Specifics of soil temperature under winter oilseed rape canopy - KRČMÁŘOVÁ, Jana; STŘEDA, Tomáš; POKORNÝ, Radovan (Contributions to Geophysics and Geodesy, 2014)
The aim of this study was to evaluate the course of soil temperature underthe winter oilseed rape canopy and to determine relationships between soil temperature,air temperature and partly soil moisture. In addition, the aim was to describe the dependenceby means of regression equations usable for pests and pathogens prediction,crop development, and yields models. The measurement of soil and near the ground airtemperatures was performed at the experimental field Žabčice (South Moravia, the CzechRepublic). The course of temperature was determined under or in the winter oilseed rapecanopy during spring growth season in the course of four years (2010 – 2012 and 2014).In all years, the standard varieties (Petrol, Sherpa) were grown, in 2014 the semi-dwarfvariety PX104 was added. Automatic soil sensors were positioned at three depths (0.05,0.10 and 0.20 m) under soil surface, air temperature sensors in 0.05 m above soil surfaces.The course of soil temperature differs significantly between standard (Sherpa and Petrol)and semi-dwarf (PX104) varieties. Results of the cross correlation analysis showed, thatthe best interrelationships between air and soil temperature were achieved in 2 hoursdelay for the soil temperature in 0.05 m, 4 hour delay for 0.10 m and 7 hour delay for0.20 m for standard varieties. For semi-dwarf variety, this delay reached 6 hour for thesoil temperature in 0.05 m, 7 hour delay for 0.10 m and 11 hour for 0.20 m. After thetime correction, the determination coefficient (R2) reached values from 0.67 to 0.95 for0.05 m, 0.50 to 0.84 for 0.10 m in variety Sherpa during all experimental years. For varietyPX104 this coefficient reached values from 0.51 to 0.72 in 0.05 m depth and from 0.39 to0.67 in 0.10 m depth in the year 2014.